Sacred wedding dance role in the novel «Sweet Darusya» M. Matios (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
In the article the sacred meaning of the wedding dance in the novel «Sweet Darusya» M. Matios. It is indicated that Hutsul dance full of rhythm, theater, and even a mystical significance – t is a coded symbol of fate newlyweds.
Keywords: wedding dance; gutsulka; mountain- мare; sacred; mystic coded mark